MULTIMEDIA ENVIRONMENT AS A FACTOR OF INFLUENCE ON THE DEVELOPMENT OF PRESCHOOL AND PRIMARY SCHOOL CHILDREN - Romenkova, Valentīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
New media and leisure activities, often referred to as the media environment, have been a powerful factor influencing the development of the modern child. More often this influence is associated with the negative consequences caused by the fascination with gadgets (weak social skills, dependence on devices, poor academic performance, etc.). The relevance of the topic of our research is due to the insufficient amount of data that would allow a) to determine the ways of development of the multimedia component of the process of upbringing and teaching children of preschool and primary school age, b) the lack of reasoned and research-based data on the influence of the multimedia environment on the child, c) to identify problems of use of new means of information and entertainment by the child; e) to find pedagogical means of preventing negative consequences that may arise in connection with the use of media by children. In the course of the study, the time of classes in the multimedia space, the structure of using various types of devices, the presence of parental control in this process and the presence of children with addiction were determined.